Capacitance spectroscopy to characterize organic fouling of electrodialysis membranes - Watkins, James E.; Pfromm, Peter H. (My University, 1999)
Fouling of electrodialysis membranes by anionic organic substances is a widely recognized problem. We report a method to characterize fouling of anion-exchange membranes by dissolved anionic organic macromolecules (sulfonated lignin). The change of the frequency-dependent electrical capacitance of commercial ion exchange membranes is used to track the fouling process in real time. The measurements are performed in an aqueous solution containing both the organic foulant, and a representative mixture of inorganic materials. This simulates an application of electrodialysis to purge inorganics from the closed water cycle of a paper machine.
Keywords: Electrodialysis; Fouling; Water treatment; Paper making